Literature as a medium for urban reflection. À propos of three nineteenth century works: "The Dream Shop" and "The Ladies' Paradise" by Émile Zola and "The Rise and Fall of Cesar Birotteau" by Honoré de Balzac (Ciudades, 2017)
"A stream of carriages was passing at a rattling pace through this gleam of light, which traversed the damp shadow of the old Saint-Roch quarter" (Zola, "The Ladies' Paradise")
Keywords: The Dream Shop; The Ladies' Paradise; Èmile Zola; The Rise and Fall of Cesar Birotteau; Honoré de Balzac